Steady-state pharmacokinetics of rilpivirine under different meal conditions in HIV-1-infected Ugandan adults. (3rd February 2015) - Lamorde, Mohammed; Walimbwa, Stephen; Byakika-Kibwika, Pauline; Katwere, Michael; Mukisa, Lillian; Sempa, Joseph B.; Else, Laura; Back, David J.; Khoo, Saye H.; Merry, Concepta
Abstract: Objectives: To investigate the effect of food on the steady-state pharmacokinetics of rilpivirine when administered as a fixed-dose combination tablet containing tenofovir disoproxil fumarate, emtricitabine plus rilpivirine (TDF/FTC/RPV) in HIV-1-infected Ugandan patients. Methods: This was an open-label, three-period, longitudinal pharmacokinetic study with patients serving as their own controls. Fifteen consenting and virologically suppressed HIV-1-infected adults were switched from an efavirenz-based regimen to TDF/FTC/RPV for 56 days. Enrolled patients underwent 24 h blood sampling with TDF/FTC/RPV dosing in the fasted state (day 42), with a low-fat meal (11 g of fat/353 kcal, day 49) and with a moderate-fat meal (19 g of fat/589 kcal, day 56; reference). A viral load assessment was performed on day 56. Results: Rilpivirine AUC0–24 was significantly decreased by 16% (geometric mean ratio, 90% CI: 0.84, 0.73–0.96) during administration in the fasted state when compared with AUC0–24 during administration with a moderate-fat meal. Similarly, rilpivirine C 24 was significantly decreased by 21% (0.79, 0.65–0.97) in the fasted state compared with a moderate-fat meal. Pharmacokinetic parameters were unchanged during administration with a low-fat meal, except for C 24, which was significantly increased by 15% (1.15, 1.01–1.31) when compared with the moderate-fat meal. Rilpivirine C max was similar under the three meal conditions. Virological suppression was unchanged at the end of the study. Conclusions: A food effect was observed for steady-state pharmacokinetic parameters of rilpivirine (AUC0–24 and C 24 ) when TDF/FTC/RPV was administered in the fasted state compared with the moderate-fat meal. The TDF/FTC/RPV formulation can be administered with either a low-fat or moderate-fat meal.